Binding of insecticidal lectin Colocasia esculenta tuber agglutinin (CEA) to midgut receptors of Bemisia tabaci and Lipaphis erysimi provides clues to its insecticidal potential. Issue 13 (30th May 2014) - Roy, Amit; Gupta, Sumanti; Hess, Daniel; Das, Kali Pada; Das, Sampa
<x xml:space="preserve">Abstract</x> The insecticidal potential of Galanthus nivalis agglutinin‐related lectins against hemipterans has been experimentally proven. However, the basis behind the toxicity of these lectins against hemipterans remains elusive. The present study elucidates the molecular basis behind insecticidal efficacy of Colocasia esculenta tuber agglutinin (CEA) against Bemisia tabaci and Lipaphis erysimi. Confocal microscopic analyses highlighted the binding of 25 kDa stable homodimeric lectin to insect midgut. Ligand blots followed by LC MS/MS analyses identified binding partners of CEA as vacuolar ATP synthase and sarcoplasmic endoplasmic reticulum type Ca2+ ATPase from B. tabaci, and ATP synthase, heat shock protein 70 and clathrin heavy chain assembly protein from L. erysimi. Internalization of CEA into hemolymph was confirmed by Western blotting. Glycoprotein nature of the receptors was identified through glycospecific staining. Deglycosylation assay indicated the interaction of CEA with its receptors to be probably glycan mediated. Surface plasmon resonance analysis revealed the interaction kinetics between ATP synthase of B. tabaci with CEA. Pathway prediction study based on Drosophila homologs suggested the interaction of CEA with insect receptors that probably led to disruption of cellular processes causing growth retardation and loss of fecundity of target insects. Thus, the present findings strengthen our current understanding of the entomotoxic potentiality of CEA, which will facilitate its future biotechnological applications.